PRINCIPAL MATERIAL RELATIONAL ANALYSIS DUCTING BASED ON THE PRICE AND CORROSION RATE MATERIALS - Zahran, Raihan Rabby; Sunardi, Sunardi; Haryadi, Haryadi; Pinem, Mekro Permana; Yusuf, Yusvardi; Demustila, Harly; Nazwa, Intan (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Ducting is a supporting component of the HVAC system. (Heating, Ventilation, and Air Conditioning). In other words, ducting can be used as an air supply, and as a channel for both cold and hot air, air drainage, air absorption, and ventilation. It is used to ensure that the air quality in the room is awakened according to the needs of the room. In the selection of material for ducting, one can consider various aspects. In this journal, the aspects considered are the corrosion rate, ultimate tensile strength, and the material price of the three types of materials, namely BJLS, aluminium, and stainless steel. Based on the results of the test and calculation, BJSL has the highest corrosion rate of about 0.62 Mpy on the 14th day, stainless steel has a corrosive rate of around 0.29 Mpy on the 14th day, and aluminum has the lowest rate of corrosiveness of about 0,27 Mpy at the 15th day.